Rising Inequality of Housing? Evidence from Segmented Housing Price Indices - Erling Røed Larsen; Dag Einar Sommervoll (Statistics Norway, Research Department, 2003)
This article uses the Case-Shiller technique for constructing housing price indices on a Norwegian data set of transactions for the period 1991-2002 consisting of 10 376 pairs of repeated sales. Using a weighted least squares scheme in order to control for heteroskedasticity, we construct a general housing price index by regressing differences in log prices for the subset of repeated sales of same, and thus identical, homes onto a set of binary time variables, one for each quarter in the period. The constructed index shows that nominal prices for identical homes in general have increased by a factor of 3.58 over the 11-year period, while the CPI increased by 1.28, creating substantial capital returns for early purchasers. We then segment the data set into five different housing types in order to control for finite mixtures of hedonic features, and find that price indices for the smallest and largest type show nominal increases by factors 4.40 and 2.77, respectively.
Keywords: C20; D40; G20; R21; 330; distribution; hedonic model; housing price bubble; housing price index; inequality; repeated sales model; segmented housing types